PERAN GURU AKIDAH AKHLAK DALAM MENANAMKAN SIKAP PERILAKU SISWA KELAS VII MTs AL-WASHLIYAH GEDUNG JOHOR - Dayani, Silvia Dwi (Fakultas Agama Islam, 2020)
Madrasah Tsanawiyah School, Gedung Johor, there are still many students who behave and have attitudes that are far from the values of Islamic teachings, such as not dressed neatly, not greeting teachers and friends, making fun of each other, not doing the tasks assigned by the teacher. and various other less praiseworthy attitudes found in the student. In an effort to improve student attitudes and behavior, the role of akidah akhlak teachers is very important in instilling moral values in students through learning and cultivating attitudes that are in accordance with the morals taught in Islam. The problem in this study is how the role of akidah akhlak teachers in instilling the attitudes and behavior of class VII students at MTs Gedung Johor. What are the attitudes and behavior of grade VII students at MTs Gedung Johor. What are the obstacles for the akidah akhlak teacher in instilling the attitudes and behavior of seventh grade students at MTs Gedung Johor. This research is qualitative in nature by collecting data through interviews with informants and descriptive analysis. The results of this study indicate that the role of the akidah akhlak teacher in instilling the attitudes and behavior of seventh grade students at MTs Gedung Johor shows a good role in accordance with their role as educators and teachers who have teacher competence, teach in accordance with the provisions set by the school and become role models for students. . Attitudes and behavior of class VII students at MTs Gedung Johor through the role of akidah akhlak teachers have good attitudes and behaviors which are marked by student compliance with rules and regulations, awareness of students in carrying out learning tasks and establishing good relationships with teachers and fellow students. There are still students who need time to understand lessons because there is no background in religious education, as well as lack of supervision from parents of students at home.